Kryzys w teorii ekonomii - Kundera, Janina Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the theories of economic crisis, divided into two groups: endogenous and exogenous theories. In the framework of the endogenous theory the concepts of demand and supply crisis, monetary and real theories were presented. An attempt was made to determine the causes of the crisis that broke out in 2008 in the United States and soon took over the whole world, and its impact on the development of economy.
Keywords: równowaga; kryzys gospodarczy; teorie endogeniczne i egzogeniczne; szoki popytowe i podażowe